Teaching the technical performance of bronchoscopy to residents in a step-wise simulated approach: factors supporting learning and impacts on clinical work – a qualitative analysis - Anne Kathrin Eickelmann (BMC, 2021)
Abstract Background The ability to perform a bronchoscopy is a valuable clinical skill for many medical specialities. Learning this skill is demanding for residents, due to the high cognitive load. Lessons learned from cognitive load theory might provide a way to facilitate this learning. The aim of this study was to investigate residents’ perception of factors that support and hinder learning, as well as outcome and acceptance of a workshop on flexible bronchoscopy. Methods Three half-day workshops were designed to teach 12 residents the basics of handling a flexible bronchoscope. They consisted of four phases that alternated between short theoretical aspects and longer practical situations. The practical phases focussed initially on manoeuvring a bronchoscope through holes in panels inside a box, and then on examination and practice using a three-dimensional printed model of the bronchial tree. Afterwards, three audio- and video-recorded focus groups were conducted, transcribed and coded, and underwent reflexive thematic analysis. Results Analysis of the focus groups defined two themes: (1) factors that supported a safe and positive learning environment were optimised for intrinsic load, simulated setting, absence of pressure, dyad practice (working in pairs), small group sizes and playful learning; and (2) impacts on clinical work were perceived as high levels of learning and improved patient safety. The residents did not report factors that hindered their learning. Some suggestions were made to improve the set-up of the wooden box. Conclusions The half-day workshop was designed according to several factors, including cognitive load theory in a simulated setting, and creation of a safe and positive learning environment. The residents perceived this as supporting learning and patient safety. Further studies can be designed to confirm these results in a quantitative setting. Trial registration This study was not interventional, therefore was not registered.